Postmortem for a postmodernist - Berger, Arthur Asa, 1933- (AltaMira Press, 1997)
You are invited to join the dectective Solomon Hunter in his hunt for knowledge and a killer. Ettore Gnocchi, the famed postmodern theorist, has been murdered at his own dinner party. To find out who killed Gnocchi, Hunter must first explore postmodernism itself.